Received Respect and Constructive Voice: The Roles of Proactive Motivation and Perspective Taking - Ng, T.W.H.; Hsu, D.Y.; Parker, Sharon (SAGE PUBLICATIONS INC, 2021)
© The Author(s) 2019. This study advances voice research by offering a social-relational view of the drivers of voice, a theoretical approach to voice that is seldom considered within the current paradigm largely focused on personality traits, job conditions, and organizational characteristics. One overlooked yet important social-relational antecedent of voice is received respect. Our core premise is that when employees believe they are respected by coworkers, they experience psychological changes to their control beliefs (representing “can-do” proactive motivation) and positive mood (representing “energized-to” proactive motivation), which then motivate voice. We further consider another social-relational variable—perspective taking—as a predictor of received respect and therefore as an indirect predictor of voice. Through a multimethod, multisample research program comprising four studies (two experiments involving more than 400 subjects in total, a sample involving more than 700 matched employee-coworker and subordinate-supervisor dyads, and a 9-week within-person field investigation of more than 400 university alumni), we provide evidence to support the proposed model. That is, received respect was associated with employees’ voice through control beliefs and positive mood, and perspective taking was a prominent predictor of received respect.